Workplace-Based Learning Outcomes Among Hospitality Students in Guangxi Vocational Colleges - Chen, Zeyu; Tang, Jia; Huang, Siyan (Research and Advances in Education, 2025)
This study investigates the learning outcomes and structural challenges of workplace-based learning (WBL) programs among hospitality students in vocational colleges in Guangxi, China. Drawing from institutional case studies, student reflections, and industry engagement, the research examines how WBL contributes to skill development, professional identity formation, and employment preparedness. Findings reveal significant gains in both technical and soft skills, but also highlight structural gaps in supervision quality, program coordination, and equitable access to high-quality placements. Institutional responses include reforms in partner selection, reflective assessment integration, and faculty capacity-building. The study proposes a sustainable model for hospitality WBL rooted in tri-sector collaboration, data-driven program design, and student-centered support mechanisms.